Terahertz radiation - Wong, Yun Ming (Nanyang Technological University, 2020)
While the world is rapidly progressing towards a digital era, it is not surprising that wireless communication is playing an increasingly significant role in the society. At the current growth rate of the data traffic volume, the fifth-generation system is expected to reach its limit in 10 years, hence necessitating the introduction of the sixth-generation (6G) system. Terahertz (THz) radiation, which has not yet been utilised for telecommunication purpose, serves as a key component for the development of the 6G system due to its potential to provide an ultra-wide bandwidth. In the context of communication, the performance of transmission line has always been a crucial element and evolution is constantly being observed, with the ultimate goal of minimising the signal loss as much as possible. From metallic waveguide to dielectric waveguide, the subject of research has now landed on a novel waveguide based on photonic topological insulator (PTI). In this project, the characterisation of a tranmission line using PTI waveguide was done in the THz region. From simulations, it was found that the transmission was higher when the couplers were placed above or below the domain wall and made to penetrate deeper into the PTI slab. The length of the PTI slab did not have a remarkable effect on the transmission, which was further confirmed by the plots of propagation loss. Last but not least, the robustness of PTI waveguide against bending loss was verified by both simulation and experiment. Owing to the great number of parameters involved in manufacturing the transmission line, more work could be done in the future to achieve an even better optimisation for transmission of signal.